The German Local Population Database (GPOP): 1871 to 2019 - Felix Rösel (Journal of Economics and Statistics, 2023)
I present the first database of historical local population figures for all Germany. The German Local Population Database (GPOP) includes total population in 1871, 1910, 1939, 1946, 1961, 1987, 1996, 2011, and 2019 for the universe of all German municipalities, counties, and states at consistent contemporary boundaries (31 December 2019). The database was hand-collected and assembled from more than 50 sources. The data reflect 150 years of regional development and disparities in Germany. For example, East and West Germany are heavily diverging in population since 1945; and the divide was not reversed but even doubled after reunification.
Keywords: J11; R11; N33; N34; 330; data; Germany; GPOP; history; population